First records of Hysterothylacium pelagicum (Anisakidae) and Toxocara alienata (Toxocaridae) from Peru - Fe de errata - Gomez-Puerta, Luis A. (2015)
An error is in the article First records of Hysterothylacium pelagicum (Anisakidae) and Toxocara alienata (Toxocaridae) from Peru published in Revista Peruana de Biologia (2014) 21 (2): 171-174. DOI: http://dx.doi.org/10.15381/rpb.v21i2.9820 The error is referred to Table 1. Some measures of Hysterothylacium pelagicum are not reported correctly. Here, present the table that should be considered.